THE INFLUENCE OF PROBLEM BASED LEARNING WITH SCIENCE, ENVIROMENT, TECHNOLOGY, SOCIETY (SETS) APPROACH TO STUDENTS’ PROBLEM SOLVING SKILLS AND ENVIRONMENTAL AWARENESS CHARACTER - Saadah, Dian Nailis; Sukaesih, Sri; Wusqo, Indah Urwatin (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2017)
This research was done in SMP 4 Kudus. This research aimed to unveil the influence of problem-based learning with SETS approach to students’ problem-solving skills and environmental awareness. This research was a quasi-experimental research with control group design. The sampling used purposive sampling technique. The samples of this research were VII A class (experiment class) and VII B class (control class). The data were collected by using tests, observation, and self-assessment. The analysis showed that problem-based learning with SETS influenced students problem-solving skills in 56.3%. Experiment class students’ problem-solving skills were better than the control class proved from the t-test analysis where tcount > ttable. Based on the analysis of man witney test, the average score of environmental awareness in control class and experiment class known as Zcount of 4.01 and Ztable of 1.96. The average percentage of students’ responses was 84.9% in a very good category. In conclusion, problem-based learning with SETS approach influences students’ problem-solving skills and their environmental awareness.